Dissection of the early steps in the assembly of the 20S proteasome in Saccharomyces cerevisiae - Matias, Ana Catarina Parreira Peres (2013)
Tese de dout., Bioquímica (Biologia Celular e Molecular), Faculdade de Ciências e Tecnologia, Univ. do Algarve, 2010